Етапи розвитку динамічної моделі діалогічної маніпулятивної ситуації - Сорокіна, Ліна Євгеніївна; Sorokina, Lina Ye. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті встановлено, що на комунікативному рівні мовленнєва маніпуляція в англомовному діалогічному дискурсі вербалізується в маніпулятивній ситуації. Динамічна модель діалогічної маніпулятивної ситуації представлена трьома етапами: домовленнєвим, мовленнєвим, постмовленнєвим, що дає змогу пояснити перебіг її розвитку, а також можливі зміни сценарію за рахунок внутрішніх механізмів та зовнішніх чинників. The article focuses on the study of the communicative level of verbal manipulation in Мodern English dialogical discourse. The research offers the dynamic model of the dialogical manipulative situation as a gradual process of manipulative influence. The dynamic model consists of three stages: preverbal, verbal, postverbal. The preverbal level is not always expressed verbally. The addressant plays the main role on the level. Verbal level of the dynamic model of the dialogical manipulative situation develops according to one out of two alternative scripts: successful / unsuccessful manipulation. Postverbal level starts when a talk stops on the addressee’s initiative or the state of his / her conceptual system changes.
The Development Stages of the Dynamic Model of the Dialogical Manipulative Situation
Keywords: діалогічна маніпулятивна ситуація; dialogical manipulative situation; динамічна модель; dynamic model; домовленнєвий етап; preverbal stage